Investigation of phytochemical profiling and biological activities of methanol extract from Eryngium billardieri: antimicrobial, antibiofilm, and anthelmintic properties - Yaghoobi, Mahdi; Moridi Farimani, Mahdi; Khan, Ajmal; Asadollahi, Mojtaba; Omrani, Marzieh; Luyten, Walter; Hu, Haibo (Frontiers in Plant Science, 2025)
The genus Eryngium, belonging to the Umbelliferae family, comprises flowering plants with various pharmacological activities, including anti-inflammatory and antidiabetic properties. However, many of these activities lack scientific evaluation. This study aimed to characterize the metabolites and evaluate the antihelmintic, antibacterial, and antibiofilm activities of a methanolic extract derived from the aerial parts of Eryngium billardieri. Metabolite characterization was conducted using LC-MS combined with a computer-assisted structure elucidation method. The extract was tested against six fungi, six Gram-positive bacteria, and nine Gram-negative bacteria, and a non-parasitic nematode (Caenorhabditis elegans). A total of thirty-three compounds were identified, with the major constituents including isorhamnetin-3-O-glucoside, phytolaccagenin, terpinolene, 3,4-dimethoxybenzaldehyde, palmitic acid, isobornyl formate, isorhamnetin, and 1,4-dimethyl-7-(1-methylethenyl)-octahydroazulene. Across all tested concentrations, Gram-positive bacteria demonstrated greater sensitivity compared to Gram-negative bacteria, with Staphylococcus aureus and Micrococcus luteus showing the highest sensitivity (IC50 values of 57.47 µg/mL and 105.8 µg/mL, respectively). Among Gram-negative strains, only Brevundimonas diminuta exhibited sensitivity. In antifungal tests, six of seven yeast strains displayed sensitivity to the extract, with Candida parapsilosis and Candida albicans being particularly susceptible (IC50 values of 11.29 µg/mL and 63.29 µg/mL, respectively). The antibiofilm analysis demonstrated inhibitory effects within 24 hours after biofilm formation, with an IC50 of 6.3 µg/mL. Additionally, the antihelmintic assay revealed a mean inhibition rate of 97.7 ± 1.5 at 2.0 µg/mL. The results demonstrate that the extract effectively inhibited the tested bacteria, particularly against yeast strains. While the extract showed promising activity against a model nematode, further research is imperative to validate its anthelmintic efficacy against parasitic nematodes.